PsycEXTRA Dataset 2001
DOI: 10.1037/e452712006-001
|View full text |Cite
|
Sign up to set email alerts
|

MRI Measurements of Craniospinal and Intracranial Volume Change in Healthy and Head Trauma Cases

Abstract: The volumes of the intracranial space and the craniospinal system as a whole change during the cardiac cycle. These volume changes are caused by the pulsatile arterial inflow to the cranium, venous outflow from the cranium, and cerebrospinal fluid (CSF) flow that oscillates back and forth between the cranium and the spinal canal. The volume changes can be measured accurately and reproducibly using a dynamic, motion-sensitive MRI technique [1]. It appears intuitive that the volume change of the entire craniospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Given that the CSF pulse reflects changes in the instantaneous volume of the arterial and venous blood flows within the cranium, (28,29) we conclude that the increased pulsatility exhibited by the aqueductal CSF flow in the MS patients probably reflects changes in blood flow dynamics through the brain parenchyma. Furthermore, given that there is no evidence of altered arterial pulse in MS patients, we postulate that changes in the CSF pulsatility may be due to alterations in the dynamics of the cerebral venous system, as demonstrated in other pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the CSF pulse reflects changes in the instantaneous volume of the arterial and venous blood flows within the cranium, (28,29) we conclude that the increased pulsatility exhibited by the aqueductal CSF flow in the MS patients probably reflects changes in blood flow dynamics through the brain parenchyma. Furthermore, given that there is no evidence of altered arterial pulse in MS patients, we postulate that changes in the CSF pulsatility may be due to alterations in the dynamics of the cerebral venous system, as demonstrated in other pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given that there is no evidence of altered arterial pulse in MS patients, we postulate that changes in the CSF pulsatility may be due to alterations in the dynamics of the cerebral venous system, as demonstrated in other pathologies. For example, it has been shown that an altered CSF pulse in head trauma patients was directly related to increased pulsatility in the cerebral venous system (28) and that increased CSF pulsatility in leukoaraiosis patients was associated with increased pulsatility in the venous sinuses (11,(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods of nICP assessment have been reported so far, like MRI-based methodology 6 7 8 21 , optic nerve sheath diameter (ONSD) 4 9 22 23 24 , and tympanic membrane displacement 25 26 27 28 . Although some of them show a high correlation with ICP, none of them have yet reached wider application in clinical practice, nor have they been able to act as a substitute for LPP.…”
Section: Discussionmentioning
confidence: 99%
“…In cerebral MRI scans, IIH is indicated by the appearance of an empty sella 5 . Although these and other MRI-based techniques 6 7 8 are used in clinical practice, they do have some limitations regarding their accuracy 9 .…”
Section: Introductionmentioning
confidence: 99%